Enhanced corrosion resistance of mild steel in 1 M HCl solution by trace amount of 2-phenyl-benzothiazole derivatives: Experimental, quantum chemical calculations and molecular dynamics (MD) simulation studies. (January 2017) - Salarvand, Zohreh; Amirnasr, Mehdi; Talebian, Milad; Raeissi, Keyvan; Meghdadi, Soraia
Graphical abstract: Highlights: Green synthesized benzothiazole derivatives as inhibitors on mild steel in 1 M HCl. The inhibition efficiency of N-dimethylbenzothiazole is >95% at 50 ppm (by weight). These benzothiazole compounds act as mixed-type and adsorption inhibitors. The conflict between experimental results and DFT is explained by MD simulation. Both the molecular electronic and structure are effective in the inhibition process. Abstract: The inhibition performance of 2-(2′-hydroxylphenyl)benzothiazole, (1 ), 2-(2′, 5′-dihydroxyphenyl)benzothiazole, (2 ), and (4-benzothiazole-2-yl-phenyl)-dimethyl-amine, (3 ), has been investigated for mild steel in 1 M HCl. Notably, compound3 shows 95% inhibition efficiency at 50 ppm (by weight) concentration. The adsorption of these compounds obeys the Langmuir adsorption isotherm with predominately chemisorption for3 and comprehensive for1 and2 . Quantum chemical calculations predicted an inhibition order of3 > 2 > 1, is at odds with the experimental order due the structural effects. Molecular dynamic simulation revealed a nearly flat configuration for molecules on metal surface with negative binding energies in a sequence agreed by the experiments, 3 > 1 > 2 .